Synergistic Cytotoxicity of 5-Fluorouracil and Epigallocatechin-3-Gallate on Colorectal Cancer Stem Cell - Ibrahim, Sugeng; Riwanto, Ignatius; Suharti, Catharina; Putra, Agung; Budijitno, Selamat (http://dharmais.co.id/, 2024)
Background: Colorectal cancer stem cells (CR-CSCs) derived from the HCT-116 cell line established human colon carcinoma cell line, validated with CD44+/CD133+. The study investigates the synergistic effects of combining epigallocatechin gallate (EGCG) with 5-fluorouracil (5-FU) on CR-CSCs through comprehensive cytotoxicity assessments, aiming to enhance therapeutic outcomes. EGCG is a polyphenol with anti-cancer activity in green tea. Previous studies have reported that the anti-cancer activity of EGCG involves inhibition of proliferation and induction of apoptosis thereby reducing recurrence by as much as 51.6% in patients with colorectal adenoma after polypectomy. The significance lies in optimizing treatment strategies by understanding the potential synergies between conventional chemotherapeutic agents and natural compounds. Given 5-FU's status as a cornerstone in CR-CSCs chemotherapy and EGCG's emergence as a promising natural compound, the study delves into their individual and combined cytotoxicity profiles. Methods: The single and combination assay aimed to determine the cytotoxicity of EGCG and 5-FU, including establishing the half inhibitory concentration (IC50) and combination index (CI) values. CR-CSCs colonies were disassociated, counted, and cultured in 96-well plates. Test solutions of varying concentrations were applied, and subsequent steps involved incubation, media removal, washing, MTT reagent addition, and absorbance measurement. Results: The single cytotoxicity tests established individual IC50 values, revealing 141.26 µM for 5-FU and 464.56 µM for EGCG. Subsequent combination cytotoxicity tests demonstrated a synergistic effect at specific doses, indicated by CI values below 1. Conclusions: These findings highlight the potential for increased cytotoxicity against CR-CSCs when treated with the combination of 5-FU and EGCG.